Human rights: their presence in Colombian Constitutions. Part I About the analysis of content of the texts corresponding to the Constitutions of 1886 and 1991 - Sierra-Baena, Miguel Ángel; Sierra-Londoño, Alonso; Zapata-Ocampo, Óscar de Jesús (Universidad Pedagógica y Tecnológica de Colombia, 2014)
As part of the research project “Interaction With Sociocultural Minorities (MSC ) in the University Traditional Context of Medellín ( 1980-2008 ): Reading from N Life Stories, sponsored by the Colombian Institute for the Development of Science and Technology Francisco José de Caldas” -COLCIENCIAS- major Colombian Constitutions, enacted between 1821 and the present, and their reforms were studied. The analysis focused on four of these Constitutions and they were chosen as research corpus, corresponding to 1886 and 1991. Rather than engage in the process of analyzing the content of the constitutional text and to motivate the subsequent discussion, this paper emphasizes the early reflections (interpretations, meanings, inferences, and contexts) of authors in the presence and processing of human rights -of first, second and third generations, especially those who may favor socio-cultural minorities-in these two Constitutions of our country.